Sleep better than medicine? Ethical issues related to “wake enhancement” - Ravelingien, A. (Journal of medical ethics, 2008)
This paper deals with new pharmacological and technological developments in the manipulation and curtailment of our sleep needs. While humans have used various methods throughout history to lengthen diurnal wakefulness, recent advances have been achieved in manipulating the architecture of the brain states involved in sleep. The progress suggests that we will gradually become able to drastically manipulate our natural sleep-wake cycle. Our goal here is to promote discussion on the desirability and acceptability of enhancing our control over biological sleep, by illustrating various potential attendant ethical problems. We draw attention to the risks involved, possible conflicts of interests underlying the development of wake enhancement, and the potential impact on accountability for fatigue related errors.